Nutritional Studies on the Evaluation of the Safety of Squilla Protein - Lekshmy Nair, A.; Madhavan, P.; Prabhu, P.V. (Fishery Technology, 2025)
Safety evaluation of squilla protein was carried out by feeding it at 10 and 20% protein levels to weanling rats for 24 weeks. Growth rate and reproductive performance of them were compared to the control animals, fed on casein at 10% protein level. Fertility of the group fed 20% squilla protein was comparable to that of the control while that of the 10% squilla protein group was lower. Average number of pups bom alive was also lower for the 10% squilla protein fed group than the other two. Significant differences were not observed in the gestation index and lactation index between the experimental and control animals. The average weight of pups at birth and on 21st day for control and 20% squilla protein group were similar while it was lower for the 10% squilla protein group. No adverse changes in appearance, behaviour and survival of the rats on experimental diets were observed.